Ultrasensitive Surface‐Enhanced Raman Spectroscopy Detection by Porous Silver Supraparticles from Self–Lubricating Drop Evaporation - Tulsi Satyavir Dabodiya; Somasekhara Goud Sontti; Zixiang Wei; Qiuyun Lu; Romain Billet; Arumugam Vadivel Murugan; Xuehua Zhang (Advanced Materials Interfaces, 2022)
Abstract This work demonstrates an original and ultrasensitive approach for surface‐enhanced Raman spectroscopy (SERS) detection based on evaporation of self‐lubricating drops containing silver supraparticles. The developed method detects an extremely low concentration of analyte that is enriched and concentrated on sensitive SERS sites of the compact supraparticles formed from drop evaporation. A low limit of detection of 10−16 m is achieved for a model hydrophobic compound rhodamine 6G (R6G). The quantitative analysis of R6G concentration is obtained from 10−5 to 10−11 m. In addition, for a model micro‐pollutant in water triclosan, the detection limit of 10−6 m is achieved by using microliter sample solutions. The intensity of SERS detection in this approach is robust to the dispersity of the nanoparticles in the drop but became stronger after a longer drying time. The ultrasensitive detection mechanism is the sequential process of concentration, extraction, and absorption of the analyte during evaporation of self‐lubrication drop and hot spot generation for intensification of SERS signals. This novel approach for sample preparation in ultrasensitive SERS detection can be applied to the detection of chemical and biological signatures in areas such as environment monitoring, food safety, and biomedical diagnostics.